The Application of The Mind Mapping Method in Improving Student Learning Achievement in Madrasah Diniyah - Imamuddin, Imamuddin; Abdullah, Walib; Muhyin, Fatihul Iqbal Maulana (Molang: Journal Islamic Education, 2023)
This study explores the Mind Mapping method in enhancing student learning outcomes at Madrasah Diniyah LPI MAKTUBA Palduding Plak-Pak Pegantenan Pamekasan. Using a qualitative descriptive approach, the research adopts phenomenology to provide a detailed depiction of the phenomena under study. Data were collected through primary sources, including interviews and observations, and secondary sources such as existing publications and reports. Triangulation methods ensured data validity and reliability. The findings reveal that Mind Mapping significantly improves comprehension, retention, and student engagement by fostering critical thinking and connecting new knowledge to existing schemas. This approach aligns with constructivist learning theories and supports the visualization of abstract concepts, making it particularly effective in religious education contexts. The research highlights essential components for successful implementation, including material identification, preparation of learning tools, active learning strategies, and effective evaluation mechanisms. Teachers play a pivotal role in facilitating this method by creating conducive learning environments, providing clear objectives, and employing innovative teaching strategies. While the findings underscore the method's flexibility and adaptability across various educational contexts, the study acknowledges limitations such as a single institutional focus and a limited sample size. Contextual factors, including institutional support and socio-economic influences, also warrant further investigation. This study contributes to the broader literature by demonstrating the applicability of Mind Mapping in religious education and emphasizes its potential for fostering critical thinking and long-term retention. Future research should explore its longitudinal effects, application across diverse subjects, and adaptations for students with special needs to maximize its impact within varied educational frameworks.